Distribuição de bivalve invasor Limnoperna fortunei (Dunker, 1857) na Bacia do Rio Prata após vinte anos (1991-2014) de sua introdução na America do Sul - Pessotto, Marco Aurélio [UNESP] (2015)
The golden mussel (Limnoperna fortunei) is a freshwater bivalve belonging to Mytilidae family. Originally from rivers and streams of China and Southeast Asia, the species was accidentally introduced in South America in 1991, in the River the la Plata estuary, probably through ballast water. From there, it dispersed to the rivers Paraguay, Uruguay and Paraná, major drainage channels of the basin. Due to its great reproductive potential, rapid growth and ability to form settlements in short time, L. fortunei cause major ecological and economic changes, such as blockage of the drainage system and water intakes of power plants and water treatment networks. This study aimed to evaluate the distribution of L. fortunei in the main water bodies of the River de la Plata Basin, as well as the possible influence of environmental conditions on the population densities. Data were obtained from samples taken in January/February and June/July 2010, with additional sampling in June 2013 and February 2014. Vertical hauls were employed with conical network of 68 μm mesh size to collect the larvae and the limnological variables (temperature, transparency, turbidity, pH, conductivity and dissolved oxygen) were simultaneously determined. It is concluded that the species dispersion process was very fast, since their arrival in the continent occurred just two decades ago and presently it is widely distributed throughout the basin (approximately 15 degrees latitude and a linear extension of 1700 km). This is explained by the high intrinsic dispersal ability of the species (free planktonic larvae), boat incrustation and broad tolerance to environmental factors. Maximum density peaks, about 60,000 ind. m-3, were found in the lower reaches of the basin, the River de la Plata ((URU/ARG), where the species was introduced. However, we refutes the hypothesis that there is a decreasing gradient of abundance in the south-north direction. Correlation analyzes indicate ...